The dance of leadership: unravelling the impact of leadership styles on employee engagement in Malaysia's private sector / Lui Jing Yi ... [et al.] - Lui, Jing Yi; Voong, Elizabeth Ai Lin; Voon, Mung Ling; Lim, Tze-Yin (2023)
The level of employee engagement maintains a pivotal influence on overall staff and career development, as well as organizational growth. By integrating leadership and social exchange theories, this study assessed whether transformational and transactional leadership styles influence employee engagement in private sector organizations operating in the Tiger Cub Economy of Malaysia. Using snowball sampling, primary data was collected from 203 private sector staff across various industries in Malaysia through the distribution of survey questionnaires. The results of correlation and regression analyses indicated that both transformational and transactional leadership significantly increase employee engagement. Though transactional leadership demonstrated a stronger effect on engagement than transformational leadership, this difference was not statistically significant. The findings enhance the understanding of the extent to which the transformational and transactional leadership styles influence employee engagement in the private sector of a developing economy and country. The implications of the findings for theory and practice are discussed in this paper, along with future research directions.